MRI assessment of experimental gliomas using 17.6 T - Schwarz, Marc A.; Pham, Mirko; Helluy, Xavier; Doerfler, Arnd; Engelhorn, Tobias (Neuroradiology, 2013)
Using ultra-high-field contrast-enhanced magnetic resonance imaging (MRI), an increase of field strength is associated with a decrease of T1 relaxivity. Yet, the impact of this effect on signal characteristics and contrast-enhanced pathology remains unclear. Hence, we evaluated the potential of a 17.6-T MRI to assess contrast-enhancing parts of experimentally induced rat gliomas compared to 3 T.